2009
DOI: 10.1051/0004-6361/200912024
|View full text |Cite
|
Sign up to set email alerts
|

The infrared emission of ultraviolet-selected galaxies fromz= 0 toz= 1

Abstract: Aims. We want to study the IR (>8 μm) emission of galaxies selected on the basis of their rest-frame UV light in a very homogeneous way (wavelength and luminosity) from z = 0 to z = 1. We compare their UV and IR rest-frame emission to study the evolution in dust attenuation with z as well as to check if a UV selection is capable of tracking all star formation. This UV selection will also be compared to a sample of Lyman break galaxies selected at z 1. Methods. We select galaxies in UV (1500-1800 Å) rest-frame … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
56
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 55 publications
21
56
3
Order By: Relevance
“…7, A FUV is plotted versus L FUV and M star . There is a decrease of the upper envelope of the dust attenuation for large L FUV in agreement with other findings based on UV selected samples at similar redshifts (Burgarella et al 2007;Buat et al 2009;Burgarella et al 2011;Heinis et al 2012). For a given UV luminosity, dust attenuation increases with stellar mass.…”
Section: The Amount Of Dust Attenuationsupporting
confidence: 92%
See 1 more Smart Citation
“…7, A FUV is plotted versus L FUV and M star . There is a decrease of the upper envelope of the dust attenuation for large L FUV in agreement with other findings based on UV selected samples at similar redshifts (Burgarella et al 2007;Buat et al 2009;Burgarella et al 2011;Heinis et al 2012). For a given UV luminosity, dust attenuation increases with stellar mass.…”
Section: The Amount Of Dust Attenuationsupporting
confidence: 92%
“…Martin et al (2007) and Buat et al (2009) studied UV selected samples up to z ∼ 1. They reported variations of A FUV as a function of the stellar mass or K-band rest-frame luminosity.…”
Section: The Amount Of Dust Attenuationmentioning
confidence: 99%
“…The discrepancy could either be explained by a larger PAH emission in distant ULIRGs or instead by the hot dust heated by a buried AGN. We note however, that part of this discrepancy could be due to uncertain local SEDs templates (Takeuchi et al 2005;Buat et al 2009). In Fig.…”
Section: Resultsmentioning
confidence: 74%
“…ISO and Spitzer studies have suggested that luminous IR galaxies (LIRGs, 10 12 > L IR /L ≥ 10 11 ) dominate global SF at z ∼ 1 (Chary & Elbaz 2001 -hereafter CE01;Le Floc'h et al 2005;Magnelli et al 2009), while submm and Spitzer data demonstrate that ultra-luminous IR galaxies (ULIRGs, L IR ≥ 10 12 L ) are equally important at z ∼ 2 (Papovich et al 2007;Caputi et al 2007;Daddi et al 2007;A&A 518, L29 (2010) Magnelli et al 2009Magnelli et al , 2010. Until the launch of the Herschel Space Observatory (Pilbratt et al 2010), these analyses relied strongly on substantial extrapolation from the mid-IR or submm or on even more uncertain corrections of the UV luminosity (Buat et al 2009;Daddi et al 2007). Our aim is to determine how accurate these extrapolations are and search for evidence of a major change in the IR properties of galaxies with increasing redshift, using the combined power of the PACS (Poglitsch et al 2010) and SPIRE (Griffin et al 2010) instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Elbaz et al (2011) show that the IR SEDs of star-forming galaxies are not evolving with redshift and that, instead, there is a much stronger dependence on the location of galaxies with respect to the galaxy MS. In addition, Buat et al (2009), by using Spitzer MIPS data, also show that the dust attenuation expressed in terms of log (L IR /L UV ) as a function of the log (L IR + L UV ), which is proportional to the SFR, seems to be redshift independent ( fig. 2 of Buat et al 2009) in particular between redshift 0 and 1 as considered in this work.…”
Section: Stellar Masses and Sfr From Sed Fittingmentioning
confidence: 91%